Angular analysis of B0 → D*- D*+s with D*+s → D+s γ decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Journal of high energy physics, 2021)
The first full angular analysis of the B0 → D*- D*+s decay is performed using 6 fb−1 of pp collision data collected with the LHCb experiment at a centre-of-mass energy of 13 TeV. The D*+s → D+s γ and D*− → D0 π- vector meson decays are used with the subsequent D+s → K+K−π+ and D0 → K+π− decays. All helicity amplitudes and phases are measured, and the longitudinal polarisation fraction is determined to be fL = 0.578 ± 0.010 ± 0.011 with world-best precision, where the first uncertainty is statistical and the second is systematic. The pattern of helicity amplitude magnitudes is found to align with expectations from quark-helicity conservation in B decays. The ratio of branching fractions [ℬ (B0 → D*- D*+s) × ℬ(D*+s → D+s γ ]/ℬ(B0 → D*− D+s) is measured to be 2.045 ± 0.022 ± 0.071 with world-best precision. In addition, the first observation of the Cabibbo-suppressed Bs → D*− D+s decay is made with a significance of seven standard deviations. The branching fraction ratio ℬ(Bs → D*− D+s)/ℬ(B0 → D*− D+s) is measured to be 0.049 ± 0.006 ± 0.003 ± 0.002, where the third uncertainty is due to limited knowledge of the ratio of fragmentation fractions.
Im Text sind "0", "*", "+" und "-" hochgestellt, "s" jeweils tiefgestellt
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, G. Frau, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und viele weitere]